Raquel Gutiérrez Sebastián y Borja Rodríguez Gutiérrez (eds.). Literatura ilustrada decimonónica. 57 perspectivas - Gutiérrez Díaz-Bernardo, Esteban (BOLETÍN DE LA BIBLIOTECA DE MENÉNDEZ PELAYO, 2013)
.